A new form of irritant rhinitis to filtering facepiece particle (FFP) masks (FFP2/N95/KN95 respirators) during COVID-19 pandemic - Klimek, Ludger; Huppertz, Tilman; Alali, Ali; Spielhaupter, Magdalena; Hörmann, Karl; Matthias, Christoph; Hagemann, Jan (World Allergy Organization journal, 2020)
Filtering facepiece particle (FFP) masks are important items of personal protective equipment in fighting COVID-19 pandemic. They shall protect the wearer of the mask from particles, droplets, and aerosols, but they also can prevent the spread of aerosol-transmitted viruses if the wearer becomes infected. Most often, FFP respirators consist of multiple layers of non-woven fabric made from polypropylene. Worldwide, FFP respirators are subject to various regulatory standards that specify physical properties and performance characteristics. During the SARS-CoV-2 pandemic, health authorities have temporarily repealed standards for respirators. We report on 46 patients that presented with rhinitis-like symptoms strongly associated to the use of FFP masks. Some of them were obliged to use FFP masks in their work environment. Nasal endoscopy showed edemata of the nasal mucosa that significantly decreased after a period of non-use of FFP masks. Subjectively reported symptom levels decreased after cessation of FFP use for 3 or more days. The presence of polypropylene fibres isolated from nasal rinsing solution was significantly associated with the use of FFP masks in our patients. Material safety and performance deregulation of FFP masks can pose a health risk. Thus, especially health care professionals and other individuals with occupational need for FFP masks should be aware of possible hazards that come with COVID-19 pandemic protection measures.